2010
DOI: 10.3201/eid1611.100401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vaccination onBordetella pertussisStrains, China

Abstract: Strains in China may differ from those in countries that have long histories of high vaccination coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 30 publications
2
26
1
Order By: Relevance
“…Allele frequencies of the virulence-associated allelic variants, fim3B , ptxA1 , prn2, and ptxP3 , have increased within the B. pertussis population in several countries [10], [12][17]. B. pertussis strains carrying ptxP3 are more capable of producing pertussis toxin (PT) than are ptxP1 strains, and the emergence of ptxP3 strains was associated with pertussis resurgence in the Netherlands [18].…”
Section: Introductionmentioning
confidence: 99%
“…Allele frequencies of the virulence-associated allelic variants, fim3B , ptxA1 , prn2, and ptxP3 , have increased within the B. pertussis population in several countries [10], [12][17]. B. pertussis strains carrying ptxP3 are more capable of producing pertussis toxin (PT) than are ptxP1 strains, and the emergence of ptxP3 strains was associated with pertussis resurgence in the Netherlands [18].…”
Section: Introductionmentioning
confidence: 99%
“…All four isolates harbored the allele combination ptxA1 ptxP1, as determined by PCR with the primers and protocol recommended for genotyping (4). The allele combination observed is common in modern Chinese isolates (5). Of the four isolates, three had the pulsed-field gel electrophoresis (PFGE) profile BpFINR9 and one had the BpSR23 profile; they belonged to the same cluster (cluster III) (6).…”
mentioning
confidence: 99%
“…Comparative genetic analysis of the genes for B. pertussis PT and pertactin (an outer-membrane protein) between epidemic isolates and the vaccine strains revealed that expansion of strains antigenically distinct from vaccine strains has occurred [340,341,[348][349][350][352][353][354]. These findings strongly implicate vaccination as a strong driving force in the continuous evolution of the B. pertussis population and may forebode the emergence of novel variants resistant to vaccination.…”
Section: Vaccines and Toxin Evolutionmentioning
confidence: 90%
“…One possible explanation for this reemergence is that the constant selective pressure imposed by immunization might have resulted in increased antigenic divergence in the remaining bacterial population. Consequently, the effects of vaccination on toxin evolution are beginning to be examined [340,341,343,[348][349][350][351][352][353].…”
Section: Vaccines and Toxin Evolutionmentioning
confidence: 99%